PENERAPAN MULTI-OBJECTIVE OPTIMIZATION ON THE BASIS OF RATIO ANALYSIS (MOORA) METHODÂ DALAM MENGEVALUASI KINERJA GURU HONORER - Sofiansyah Fadli; Khairul Imtihan (LPPM STMIK Lombok, 2019)
The role of the teacher is very important in the learning process, also advancing the world of education. Because the quality of the teacher becomes a very important aspect, teachers must have competencies that comply with national education standards in order to perform their duties and roles with competency standards that can lead learners to Human beings with knowledge and ability. According to the guidebook for the selection of high achieving teachers, the selection of high achieving teachers to increase the motivation of teachers to improve their professionalism. The selection of outstanding teachers starts from the education unit, Regency/City, province to National. On the basis of why. The government appreciates outstanding teachers as outlined in RI Law No. 14 of 2005 concerning Teachers and Lecturers article 36 paragraph (1) which says that